Evaluation of cytokines and soluble adhesion molecules in patients with newly diagnosed acute myeloid leukemia: the role of TNF-alpha and FLT3-ITD - Kupsa, Tomáš; Vaněk, Jan; Vašatová, Martina; Karešová, Iva; Žák, Pavel; Jebavý, Ladislav; Horáček, Jan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
OBJECTIVES: Acute myeloid leukemia (AML) cells are highly resistant to therapy. The presumed molecular basis of this resistance is the effect of tumor necrosis factor alpha (TNF-α) and other cytokines on endothelial adhesion molecule expression. The aim of this study was to test the hypothesis that cytokines and soluble adhesion molecules correlate in AML. METHODS: Baseline serum levels of 17 cytokines and 5 soluble adhesion molecules were measured in 53 AML patients using biochip array technology. Age, leukocyte count, secondary AML, CRP, FLT3-ITD and remission were variables. Statistical analysis was performed in R version 3.1.2. RESULTS: VCAM-1 correlated with ICAM-1 (P < 0.0001), E-selectin (P < 0.0001), leukocyte count (P = 0.0005) and TNF-α (P = 0.0035). E-selectin correlated with leukocyte count (P < 0.0001), P-selectin (P = 0.0032) and MCP-1 (P = 0.0119). CRP correlated with IL-6 (P < 0.0001), leukocyte count negatively correlated with IL-7 (P = 0.0318). FLT3-ITD was associated with higher E-selectin (P = 0.0010) and lower IL-7 (P = 0.0252). Secondary AML patients were older. Failure of induction therapy was associated with significantly higher CRP and lower P-selectin. Leukocyte count (P < 0.0001), FLT3-ITD (P = 0.0017) and secondary AML (P = 0.0439) influenced the principal component. CONCLUSIONS: Leukemic cells can modulate the microenvironment. Cytokine, adhesion molecule levels and leukocyte count correlate in AML. Understanding these mechanisms may form the basis of novel therapeutic approaches.
Keywords: Leukocyte Count; Prospective Studies; cytokiny; Leukemia, Myeloid, Acute; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; lidé středního věku; prospektivní studie; akutní myeloidní leukemie; Middle Aged; chemorezistence; Cytokines; Cell Adhesion Molecules; fms-Like Tyrosine Kinase 3; TNF-alfa; mužské pohlaví; počet leukocytů; Drug Resistance, Neoplasm; Tumor Necrosis Factor-alpha; ženské pohlaví; analýza hlavních komponent; Principal Component Analysis; lidé; tyrosinkinasa 3 podobná fms; Male; molekuly buněčné adheze; Female